Minimizing inequality versus maximizing joint gains: On the relation between personality traits and different prosocial motivations - Mischkowski, Dorothee; Thielmann, Isabel; Glöckner, Andreas (Journal of research in personality, 2019)
•Inequality Aversion and Joint Gain Maximization are opposing prosocial motivations.•We investigated the relation of these motivations with (basic) personality traits.•We consider whether inequality is initially advantageous for the self or the other.•Honesty-Humility was positively related to inequality aversion.•The relation was (slightly) stronger when inequality was advantageous for the self. The Social Value Orientation (SVO) Slider Measure allows a differentiation between two prosocial motivations: minimizing inequality versus maximizing joint gains. In two studies (N = 1202), we investigated the relation between this suggested continuum from Inequality Aversion (IA) to Joint Gain Maximization (JGM), the HEXACO personality dimensions, and SVO. To account for differences in fairness perception, we also considered whether inequality favored oneself or the other. As hypothesized, Honesty-Humility was the best basic trait predictor of IA, showing a slightly stronger positive link when inequality was self-advantageous. SVO, in turn, showed a stronger (negative) link when inequality was disadvantageous for the self. Overall, the results show that IA is related to (basic) personality traits in a theoretically meaningful way.